PERTUMBUHAN DAN HASIL JAGUNG MANIS (Zea mays Saccharata Sturt.) YANG DITANAM DENGAN TANAMAN SELA PEGAGAN (Centella asiatica (L.) Urban) PADA BEBERAPA TARAF DOSIS PUPUK ANORGANIK - Sarjan Alatas; Irsyadi Siradjuddin; Mokhamad Irfan; Aulia Rani Annisava (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
The problem of agricultural crops cultivation today is the productivity of land that has not been optimally, where the availability of land among the main crops should be utilized maximally by planting intercrops. This research aims to determine the cropping patterns and the best of inorganic fertilizers dosage, well as the interaction of cropping patterns with inorganic fertilizer to the growth and yield of sweet corn. The research was conduted from November 2017 until January 2018 in the village of Dundangan, district of Pangkalan Kuras, Pelalawan regency and Agronomic Laboratory of Faculty of Agriculture and Animal Science, Universitas Islam Negeri Sultan Syarif Kasim Riau. This research uses Randomized Block Design (RBD) with two factors and three replications. The first factor is cropping pattern with two levels that is cropping pattern of sweet corn monoculture and cropping pattern of sweet corn with pegagan plant. The second factor is the application of inorganic fertilizers with three levels is 0%, 50% and 100% recommended dosage. The results showed that the cropping pattern of sweet corn planted with intercropping pegagan gave the same results as good with the croping pattern of sweet corn monoculture, except on the parameter of leaf age of 6 weeks after plant which yield more leaf number on monoculture cropping pattern. Inorganic fertilizers application 50% recommended dosage (Urea 250 kg/ha + TSP 175 kg/ha + KCl 150 kg/ha) increased yield weight of corn cobs weighted per plot, corn cob weight without weight per cob and weight of corn cobs without weight per plot.There is not interaction between cropping patterns and inorganic fertilizers on the growth and yield of sweet corn crops.